Acousmatic Park - Interacção com o espaço sonoro, natureza e modos de escuta - Francisca Santos Silva Rocha Gonçalves (2016)
A sound space is bound to the individual as a listener and to the state of their auditory surroundings. We are in a complex sonic exchange with our environments, making, muting, altering and auditing sound. In a context where the impact of sound in our society is increasingly relevant, creating a distance from the natural world and its sounds, it is important to raise sensibility in the individual to a new approach to the listening process, encouraging aural learning and expanding our auditory consciousness. Regarding this problema, we describe the research process on the development and implementation of a site-specific sound installation in Casa da Música named Acousmatic Park. Our main motivations are to increase our aural awareness; enhance the relationship between sound and the hearing process by exploring the different listening modes; encourage listening exercises in order to promote awareness to the environmental sounds and promote environmental education. We pretend to create interaction between the sound space, nature and the conscious participation of the listener through the exploitation of listening modes. We believe this process helps to exercise our sound perception at a deeper level in order to develop greater awareness of the sounds around us. We present the project from an early stage of recognition and analysis of space, to its practical implementation, describing the intermediate stages. In order to increase our connection with the natural environment, the sounds used in the installation are sounds from nature, and were obtained from original recordings and also sound libraries. With this research we will understand if by building interactive sound installations we can promote and raise the aural awareness in society. Therefore we will also bring an educational interest to the community, offering a creative listening experience and a better understanding or identification of species. With the development of sound compositions, we try to recreate lost or forgotten natural environments and contribute to the preservation of sound memory in the contemporary world. Through a qualitative approach essentially based on practice based research we obtain relevant information to promote discussion and evaluate the role of listening in our society and we also propose ways to make it a more conscious act.